What would make children read for pleasure more frequently? - Merga, Margaret (2017)
Â© 2017 National Association for the Teaching of English Regular recreational reading offers benefits across a range of literacy outcomes, as well as supporting learning in other subject areas, offering cognitive benefits, and potentially fostering empathy. Therefore, increasing frequency of engagement in recreational reading can play an important role in addressing inequity in literacy outcomes once independent reading skill has been achieved. While previous studies address how to increase children's engagement in reading for recreation, few allow children's viewpoints to take primacy. The 2016 Western Australian Study in Children's Book Reading collected data from respondents across 24 schools, seeking to determine how educators and parents may best support young people to read with greater frequency. Interview participants from Years 4 and 6 were asked what would make them read more. The five recurring themes of finding engaging books, series adherence, challenge seeking, skill deficit, and time availability indicate optimal avenues for future research and educational intervention to foster increased engagement in reading.